The study of children’s physical activity - Pagels, Peter; Boldemann, Cecilia; Raustorp, Anders (Socialmedicinsk tidskrift, 2013)
Preschool children's physical activity has an important health promoter against several of the lifestyle diseases. Therefore it is important that the preschool environment encourages preschool children to a healthy physical activity. In the Kidscape project we studied preschool children's physical activity during their stay at the preschool. The aim was to identify factors in the outdoor environment that influence children's activity patterns. Activation patterns were studied with both subjective methods (CARS and qualitative observation) and objective methods (pedometri and accelerometry). The results showed that preschool children's physical activity was higher in preschools with a good schoolyard environment. Conclusion: preschool outdoor environment can promote a healthy physical activity in preschool children.